2001
DOI: 10.1080/10485250108832852
|View full text |Cite
|
Sign up to set email alerts
|

Model robust regression: combining parametric, nonparametric, and semiparametric methods

Abstract: In obtaining a regression tit to a set of data, ordinary least squares regression depends directly on the parametric model formulated by the researcher. Ifthis model is incorrect, a least squares analysis may be misleading. Altematively, nonparametric regression (kemel or local polynomial regression, for example) has no dependence on an underlying parametric model, but instead depends entirely on the distances between regressor coordinates and the prediction point of interest. This procedure avoids the necessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 42 publications
2
29
0
2
Order By: Relevance
“…when cost of data collection is prohibitive), nonparametric fitting techniques may fit irregularities in the data too closely, thereby creating estimated mean and variance functions which are highly variable. Mays et al (2001) (henceforth referred to as MBS) introduce semi-parametric methods for estimating the mean in constant variance situations, which are essentially hybrids of parametric and nonparametric methods. Pickle et al (2008) extend the method of MBS to the dual model problem for the replicated case.…”
Section: Overview Of Dual Model Regressionmentioning
confidence: 99%
“…when cost of data collection is prohibitive), nonparametric fitting techniques may fit irregularities in the data too closely, thereby creating estimated mean and variance functions which are highly variable. Mays et al (2001) (henceforth referred to as MBS) introduce semi-parametric methods for estimating the mean in constant variance situations, which are essentially hybrids of parametric and nonparametric methods. Pickle et al (2008) extend the method of MBS to the dual model problem for the replicated case.…”
Section: Overview Of Dual Model Regressionmentioning
confidence: 99%
“…We adopt here to the mixed model scenario a penalized version of PRESS, proposed in the context of fixed effects models for uncorrelated data by Mays et al [31] For the LM model, PRESS * * is defined as…”
Section: Press * *mentioning
confidence: 99%
“…Since tr [H k ] reflects the kernel fits' " model degrees of freedom" (Cleveland, 1978), it is seen that the denominator of PRESS*(6) penalizes the PRESS statistic for choosing b too small. Empirical studies by the authors and others (Einsporn and Birch, 1993;Mays, 1995) have demonstrated that using PRESS*(b) is often superior to using PRESS as a bandwidth selector.…”
Section: Nonparametric Modelsmentioning
confidence: 99%